2011
DOI: 10.1159/000331794
|View full text |Cite
|
Sign up to set email alerts
|

Oral Findings and Salivary Parameters in Children with Celiac Disease: A Preliminary Study

Abstract: Objective: The aim of this study was to investigate the prevalence of dental enamel defects, recurrent aphthous stomatitis (RAS) and caries experience and to measure salivary flow rate, buffer capacity, saliva and plaque pH and salivary cariogenic microflora in patients with celiac disease (CD) compared to healthy subjects. Subjects and Methods: Thirty-five patients, aged 6-19 years, with a diagnosis of CD and 35 healthy children of the same age participated in the study. Enamel defects were diagnosed and clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
69
1
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 48 publications
7
69
1
14
Order By: Relevance
“…Developmental defects of the dental enamel are especially frequently observed [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Impairment of dental crowns mineralization may occur in numerous systemic diseases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Developmental defects of the dental enamel are especially frequently observed [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Impairment of dental crowns mineralization may occur in numerous systemic diseases.…”
mentioning
confidence: 99%
“…Other complications observed in the oral cavity in patients with celiac disease are disturbances within mucosa. Aphthae are observed particularly often (RAS -recurrent aphtous stomatitis) ( Table 2) [7,9,11,12,16,18]. Cheng et al directed attention to frequent coexistence of aphthaes, and disturbances of dental enamel mineralization [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have evaluated the effects of celiac disease on the salivary parameters of affected patients. Acar et al [40] evaluated the salivary parameters of patient with celiac disease and compared the findings with those for healthy individuals; they found a lower prevalence of salivary mutans streptococci and lactobacilli colonization in celiac disease patients than in healthy individuals, with no significant differences in other parameters such as the salivary flow rate, pH, and buffering capacity [40]. In contrast, Tian et al [61] found a higher prevalence of lactobacilli with a higher glutenase activity in celiac disease patients, which may play a role in the pathogenicity of the disease [61].…”
Section: Other Oral Manifestationsmentioning
confidence: 99%
“…The oral features of celiac disease are varied and atypical, and affected patients may exhibit enamel defects, delayed tooth eruption, and impaired mandibular jaw growth [27]. Among the oral manifestations of celiac disease, enamel defects and RAS are the most common and well documented in several studies (Table 1) [29,[31][32][33][34][35][36][37][38][39][40].…”
Section: Oral Manifestationsmentioning
confidence: 99%